RECONSTRUCTION OF NAHAK MAROE RAI HERO'S POWER TO CONQUER THE NETHERLANDS IN BELU 1900-1906 - Diana Rohi; Moses Kollo (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2022)
The war that brought together the hero Nahak Maroe Rai and Dutch troops in South Belu in 1900-1906 was an effort to protect the territory of the Wewiku Kingdom from Dutch rule. The purposes of this study are to describe (1) the background of the Hero Nahak Maroe Rai in the War against the Dutch in Belu God 1900-1906; (2) The Process of the War Between the Heroes of Nahak Maroe Rai against the Dutch in Belu God 1900-1906. This study uses the historical method which includes four stages, namely heuristics, source criticism, interpretation and historiography. The results of the study revealed (1) that the background of the hero Nahak Maroe Rai led all the people of the South Wewikudi Belu Kingdom, Malacca Regency because the Dutch wanted to control the Wewiku Kingdom area; and (2) the war between the people of the Wewiku Kingdom under the leadership of Meo (hero) Nahak Maroe Rai against the Dutch troops occurred three times, namely the first resistance occurred in 1900, then the second battle occurred in 1903. In the first and second battles, The Dutch were successfully repulsed by Nahak Maroe Rai and his troops. For this reason, Nahak Maroe Rai is called by the people of the Wewiku Kingdom as a Meo (hero). In the third battle, in 1906, Nahak Maroe Rai died as a result of being hit by gunfire from Dutch troops; (3) the natural strength of the traditional house owned by Nahak Maroe Rai and the Wewiku people became a factor in the defeat of the Dutch troops.